Noninvasive molecular biomarkers for the detection of colorectal cancer - Kim, Hye-Jung; Yu, Myeong-Hee; Kim, Hoguen; Byun, Jonghoe; Lee, Cheoju (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2008)
Colorectal cancer (CRC) is the third most common malignancy in the world. Because CRC develops slowly from removable precancerous lesions, detection of the disease at an early stage during regular health examinations can reduce both the incidence and mortality of the disease. Although sigmoidoscopy offers significant improvements in the detection rate of CRC, its diagnostic value is limited by its high costs and inconvenience. Therefore, there is a compelling need for the identification of noninvasive biomarkers that can enable earlier detection of CRC. Accordingly, many validation studies have been conducted to evaluate genetic, epigenetic or protein markers that can be detected in the stool or in serum. Currently, the fecal-occult blood test is the most widely used method of screening for CRC. However, advances in genomics and proteomics combined with developments in other relevant fields will lead to the discovery of novel non invasive biomarkers whose usefulness will be tested in larger validation studies. Here, noninvasive molecular biomarkers that are currently used in clinical settings and have the potential for use as CRC biomarkers are discussed. [BMB reports 2008; 41(10): 685-692]
Keywords: FECAL-OCCULT-BLOOD; ABERRANT CRYPT FOCI; SERUM TUMOR-MARKER; COLON-CANCER; TISSUE INHIBITOR; K-RAS; POTENTIAL MARKER; DNA METHYLATION; EUROPEAN GROUP; P53 MUTATIONS